(untitled) (Globalization and Business, 2023)
In order to provide high quality primary health care system, qualified family doctors are needed. An extremely low number of properly qualified family physicians is a worldwide problem. Countries are using various strategies in order to solve this problem, for instance, they are encouraging medical students to choose family medicine as a profession. Despite these attempts, family medicine still struggles with a lack of interest, while the determination to choose a special career is increasing. According to studies, a very small number of undergraduate medical students chose family medicine as a profession. The decision to become a family doctor is influenced by the following characteristics: age, sex, family status, rural life. Studies show that students who choose family medicine are more likely to be socially oriented, instead of seeking leadership opportunities, they have a strong desire to help people and have an opportunity to take a residency in an easy way and obtain a doctor's certificate in a relatively short period of time. Students who choose the doctor’s profession are influenced by the following factors: prestige, intellectual level, payment method, income, researching opportunities, and faculty status, work-life balance. Compared to family doctors, specialists can get quite high salary for performing “high-tech” procedures. The aim of the research is to assess the attitude of medical students towards the family doctor profession, and to find out the reasons that influence medical students’ choice. According to our study, In Georgia, like in many countries, the specialization of family medicine suffers from a lack of interest, which has a negative impact on the number of properly qualified family doctors. According to our study only 2.9% of students expressed interest in the family doctor profession. The decision to become a family doctor is influenced by numerous factors: a duration of residency, an ability to form long-term relationships with patients, the influence of family or community, an ability to solve multiple medical problems, the simplicity of medical practice, an opportunity to find a job, the advantage of working in rural areas, an ability to balance career and personal life. The family doctor profession is less popular in Georgia, which is mainly caused by society’s stereotypical attitudes. To popularize the family doctor profession, it is necessary to introduce effective methods of their financing, to develop a flexible model of family medicine residency education, which would be based on the improvement of a continuous, professional practice.